Uncertain Knowledge. Studying “Truth” and “Conspiracies” in the Digital Age - Boullier, Henry (2021)
It is nowadays commonplace to find statements about how the web has increased the circulation and reach of “conspiracy theories”. In France, the attack on the Capitol by .QAnon activists in January 2021, and before that the attacks of 2015, or the surveys commissioned by the Jean Jaurès Foundation, have fueled many alarming discourses about the spread of “fake news” on the internet. The pandemic context in which we have been living since March 2020, which is marked by a high level of uncertainty and the complex intertwining of scientific, political, and geostrategic controversies, has strengthened the grip of the notion that the internet and social media now massively contribute to the disinformation of the public.